Building a Sustainable Future : The Africa Region Environment Strategy - World Bank (Washington, DC, 2013)
This environment strategy outlines the current thinking in the World Bank Group Africa Region about priorities and actions for the institution in the environmental arena. The Africa Region Environment Strategy (ARES) outlines the Bank's commitment to help its clients achieve sustainable poverty reduction through better environmental management. It identifies the most urgent issues at the interface of environment and poverty and discusses targeted actions for addressing them. It reviews the lessons from experience to date and proposes new approaches. The strategic context in which the ARES has evolved and will be implemented is defined by the Bank's mission statement and operational policies, the World Bank Environment Strategy (WBES), and by the Bank's broader objectives, priorities, and strategies in the Africa Region. Like the WBES, the ARES approaches environment through a "poverty lens" and targets four main objectives: a) ensuring sustainable livelihoods, b) improving environmental health, c) reducing vulnerability to natural disasters, and d) maintaining local, regional, and global ecosystems and values. Key elements of the ARES include integrating environment into development and poverty reduction strategies; building an enabling environment and the institutional and human capacity for sustainable environmental management; promoting environmentally sustainable and equitable private sector-led economic development; improving governance; and encouraging decentralization.